The Prosecution Project: Understanding the Changing Criminal Trial Through Digital Tools. (22nd August 2016) - Finnane, Mark; Piper, Alana
Abstract : The Prosecution Project <https://prosecutionproject.griffith.edu.au/ > is a large-scale digital project that aims to provide a new way of exploring the context and impact of changes in the criminal trial during the nineteenth and twentieth centuries. It does so from an elementary platform: the digitization of the court calendars of criminal trials in the higher courts in the six main Australian jurisdictions over time periods as long as 130 years. The objective is to address questions of the criminal justice process centered on prosecution, from arrest, committal, and indictment, to verdict, sentence, and beyond. In a field of historical research that is more often characterized by the richness of discursive analysis, the Prosecution Project's comparative data sets are designed to offer a new understanding of quantitative context over long periods of time. The challenge of building the data platform is, however, considerable, requiring significant planning, collaboration and investment by a large number of researchers, working with relevant archive repositories, and, in this case, assisted by the engagement of an interested community lying outside the regular academy. This article describes the background to the project, its development as a collaborative digital initiative, and its technical and organizational requirements and possibilities, before we explore briefly some of the research outcomes that this project makes possible.